The origin of the ‘blue tilt’ of globular cluster populations in the E-MOSAICS simulations - Usher, Christopher; Kruijssen, Diederik; Reina-Campos, Marta (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. The metal-poor subpopulation of globular cluster (GC) systems exhibits a correlation between the GC average colour and luminosity, especially in thos